Pendidikan Kristen Berbasis Alkitabiah: Membangun Fondasi Iman dan spiritualitas Terhadap Generasi Era Digital - Ondang, Anastasia Gabrielle; Ngesthi, Yonathan Salmon Efrayim (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2024)
Christian education today faces many new challenges in developing a solid foundation of faith and spirituality in the generation in the digital age. This research article explores an approach that is based on Biblical values in shaping faith and spirituality in the context of modern technology. context of modern technology. Through descriptive qualitative methods and theological analysis in the literature review, the researcher highlights the importance of the importance of integrating Biblical principles in Christian education in order to reach and shape a digitally connected generation. And the conclusion in this study provides an understanding of the importance of the challenges and opportunities of the Digital Age in Christian Education. The Digital Age in Christian Education can be used as an opportunity to apply Biblical Principles in the Digital Context. Biblical Principles in the Digital Context, so that the church can actualize the Role of Church and Family in Christian Education. actualize the Role of the Church and Family in Digital Education that strengthen the foundation of faith and spirituality amidst the flow of information and moral challenges posed by the digital era. moral challenges posed by the digital age. Thus, this article thus provides a holistic and relevant view for Christian education practitioners in facing the dynamics of the evolving times. in facing the dynamics of an ever-evolving age.AbstrakPendidikan Kristen saat ini menghadapi banyak tantangan baru dalam mengembangkan fondasi iman dan spiritualitas yang kokoh pada generasi di era digital. Artikel penelitian ini bertujuan mengeksplorasi pendekatan yang berbasis nilai-nilai Alkitabiah dalam membentuk iman dan spiritualitas dalam konteks teknologi modern. Melalui metode kualitatif deskritif dan analisis teologis dalam kajian kepustakaan, peneliti menyoroti pentingnya mengintegrasikan prinsip-prinsip Alkitabiah dalam pendidikan Kristen untuk menjangkau dan membentuk generasi yang terhubung secara digital. Dan kesimpulan dalam penelitian ini memberikan pemahaman akan pentingnya tantangan dan peluang Era Digital dalam Pendidikan Kristen yang dapat dijadikan kesempatan untuk menerapkan Prinsip-prinsip Alkitabiah dalam Konteks Digital, sehingga gereja dapat mengaktualisasi Peran Gereja dan Keluarga dalam Pendidikan Digital yang memperkuat fondasi iman dan spiritualitas di tengah arus informasi dan tantangan moral yang ditimbulkan oleh era digital. Dengan demikian, artikel ini memberikan pandangan yang holistik dan relevan bagi praktisi pendidikan Kristen dalam menghadapi dinamika zaman yang terus berkembang.